Desempenho e comportamento ingestivo de cordeiros alimentados com dietas contendo níveis de fibra - Pereira, Danillo Marte (2018)
The objective of this study was to determine the ideal dietary neutral detergent fiber (NDF) content that provides the maximization of the productive performance and the ingestive behavior of the Santa Inês sheep finished in feedlot. Thirty Santa Inês sheep were used, with an initial live weight of 23 ± 1.5 kg, distributed in a completely randomized experimental design (DIC), with twelve replicates. The diets were composed of tifton 85 hay grass (Cynodon sp.) And concentrate, and treatments were represented by neutral detergent fiber (NDF) levels (20, 32, 44, 56 and 68% NDF in DM). The supply of increasing levels of neutral detergent fiber (NDF) in the sheep diet altered quadratic (P <0.05) the intake of dry matter (IDM), organic matter (IOM) and crude protein (ICP) expressed in g / day. There was a quadratic effect (P <0.05) on the digestibility of CP and NDF. A quadratic effect was observed for weight gain (WG), daily mean gain (ADG) and feed efficiency (FE). A linear behavior was observed for time spent in feeding and rumination activities in min / day. However, a decreasing linear behavior was observed for the time spent in the leisure activity min / day as the dietary NDF levels were increased. A linear behavior was observed for the variables in relation to the mericized chews. There was no significant effect on the feed efficiency expressed in g DM/h. however, a quadratic change in feed efficiency expressed in g NDF/h was observed. There was a linear decrease in rumination efficiency, expressed in g DM/h, with the increase in NDF levels. However, the increasing NDF level in the diet influenced linearly the ruminating efficiency DM/h. There was no difference in the observations of the number of periods / day of feeding, rumination and leisure. However, a linear decrease was observed for the time spent per period (in minutes) of idle. For Santa Inês sheep destined for feedlot and fed diets based on tifton 85 hay grass, 27 to 30% of neutral detergent fiber in the dry matter of the feed is recommended.